The Role of Electronic Documents during the Formation of the Collections of Personal Origin: Foreign Experience - Ostapchuk Valeriia (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the study is to analyze the research literature deals with the use of electronic documents in the formation of archival collections of personal origin, published abroad. The research methodology is based on the systematic and combined use of scientific principles and methods. The research applied the principles of historicism, objectivity, systematicity, comprehensiveness, as well as the methods of bibliographic heuristics, analysis and synthesis, comparison and generalization, which made it possible to identify a range of scientific works, the authors of which touch on the problem of using electronic documents in the formation of collections of personal origin, and analyze their content. The scientific novelty consists in the analysis of scientific literature devoted to the use of documents of personal origin in electronic form during the formation of personal archival collections. Understanding the impact of digitalization, which is currently taking place in almost all spheres of human activity, questions arise regarding the formation, preservation and use of personal documents in electronic form, and the growing risk of their loss. In this matter, the experience of foreign researchers is valuable for developing effective approaches to further strategy. Conclusions. First of all, it is expedient to select certain groups of collections’ founders according to the field of activity and to develop practical recommendations for them on the formation of personal documents in electronic form even at the stage of personal archives. Secondly, it makes sense when describing documents of a significant volume with a fairly simple value examination (video files, photos), to transfer them to IT specialists. And more diverse documents (scientific articles, musical works, correspondence, etc.) should first be handed over to the archivists. Thirdly, copyright issues need to be refined and the necessary methodology developed.